2015
DOI: 10.4238/2015.august.21.4
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of luteinizing hormone receptor, androgen receptor and heat-shock protein 70 in the testis of long-distance transported mice

Abstract: ABSTRACT. Spermatogenesis, is a complex process of precisely regulated intracellular events, where it is affected by many factors. Long-distance transport of animals is one of the stressors that may influence spermatogenesis and sperm quality. The present study chose luteinizing hormone receptor (LHR), androgen receptor (AR), and heatshock protein 70 (HSP70) as our target genes to investigate their mRNA and protein expression in the testes of long-distance transported (about 1000 km) mice. Histological analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Therefore, quantitative (decline of the gene or protein expression) and qualitative (chromosomal defect) changes in AR could be one of the causes of male infertility. A study reported that in long-distance transported stress mice model, the mRNA and protein expression levels of AR and epididymis sperm count decreased compared with the values in the control group [39]; this result is consistent with our findings. This suggested that stress adversely affects reproductive organs and spermatozoa in adults by decreasing AR expression.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, quantitative (decline of the gene or protein expression) and qualitative (chromosomal defect) changes in AR could be one of the causes of male infertility. A study reported that in long-distance transported stress mice model, the mRNA and protein expression levels of AR and epididymis sperm count decreased compared with the values in the control group [39]; this result is consistent with our findings. This suggested that stress adversely affects reproductive organs and spermatozoa in adults by decreasing AR expression.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, LH may affect fructose utilization, glucose oxidation, and adenyl cyclase activity in sperm, which are important means by which spermatozoa derive energy for motility [20]. The acquisition of sperm motility occurs during sperm maturation in the epididymis, and LH receptors have been detected in epididymal epithelium [21,22]. Moreover, in the absence of LH, addition of TT and FSH can only partly rescue the phenotype of abnormal sperm [23].…”
Section: Discussionmentioning
confidence: 99%